Circular RNA MTCL1 targets SMAD3 by sponging miR-145‐5p for regulation of cell proliferation and migration in Hirschsprung’s disease - Chen, Wang; Caiyun, Luo; Yang, Yang; Xinwei, Hou; Nan, Li; Jiaming, Yang; Huirong, Yang; Kai, Wu; Liucheng, Yang (Pediatric surgery international, 2023)
Background Hirschsprung’s disease (HSCR) is a congenital disorder resulting from abnormal development of the enteric nervous system (ENS). Given the complexity of its pathogenesis, it is important to investigate the role of epigenetic inheritance in its development. As Circ-MTCL1 is abundant in brain tissue and colon tissue, whether it has a significant part in the development of ENS is worth exploring. This study clarifies its role in HSCR and identifies the specific molecular mechanisms involved. Methods Diseased and dilated segment colon tissues diagnosed as HSCR were collected for the assessment of gene expression levels using RT-PCR. EdU and CCK-8 assays were adopted to evaluate cell proliferation, and Transwell assay was adopted to assess cell migration. The interaction between Circ-MTCL1, miR-145-5p and SMAD3 was confirmed by dual luciferase reporter gene analysis, RT-PCR and Western blotting. Results Circ-MTCL1 was down-regulated in the aganglionic colon tissues. The decreased expression of Circ-MTCL1 associated with a reduction in cell migration and proliferation. Bioinformatics analysis and cellular experiments confirmed its role might have been associated with the inhibition of miR-145-5p. MiR-145-5p was up-regulated in HSCR diseased segment colon tissues, exhibiting a negative correlation with Circ-MTCL1. Overexpression of miR-145-5p reversed the inhibition of cell migration and proliferation associated with Circ-MTCL1 down-regulation. The expression of SMAD3 was inhibited by miR-145-5p. The overexpression of SMAD3 eliminated the miR-145-5p-associated inhibition of cell migration and proliferation. Overexpression of miR-145-5p reversed the inhibitory effects of Circ-MTCL1 down-regulation-associated inhibition of cell migration and proliferation, while suppressing SMAD3 expression. Conversely, overexpression of SMAD3 counteracted the miR-145-5p-associated inhibition of cell migration and proliferation. Conclusions Circ-MTCL1 may function as a miR-145-5p sponge, regulating the expression of SMAD3 and influencing cell migration and proliferation, thus participating in the development of HSCR.